Estudos para a determinação eletroquímica de aril N-metil carbamatos totais em águas em sistema de análise por injeção em fluxo - Azevedo, Eduardo Ferreira de (2007)
A method was investigated for the indirect electrochemistry determination of total aryl N-methylcarbamates in water through the oxidation of the phenolic derivative produced in the alkaline hydrolysis of these pesticides. As model pesticide was used Carbofuran that produces in the alkaline hydrolysis the phenolic derivative denominate as Benzofuranol (BF). The electrochemical behaviour and the analytical parameters of the determination of BF were investigated by using linear voltammetry, differential pulse voltammetry and amperometry in FIA system. The FIA system was composed by an acrylic injector switch, a flowing electrochemical cell of three electrodes, on wall-jet mode, and a propulsion system of carrier electrolyte and of sample solution towards electrochemical cell. The propulsion system was constituted by an air mini-compressor used in aquarium associated to the a water column to control the flow of carrier electrolyte. The best conditions of the amperometric determination of BF in FIA system were: acetate buffer as carrier electrolyte under flow of 2.0 ml L-1, sample volume of 200 μL and applied potential of 0.75 V vs Ag/AgCl. Carbon paste electrode (CPE) was evaluated in terms of stability of the analytical signal and reproducibility of the analytical curve. The peaks current of a group of 18 consecutives injections of BF solution showed a relative standard deviate of 2.6%. The sensibility of electrode response was stable, showing the good performance of the carbon paste electrode in these experimental conditions. The amperometric signal was linear over the concentration range 1.4x10-7 to 7.1x10-7 mol L-1of Carbofuran with detection limit and of quantification limit of of 7x10-9 mol L-1 and 2,3x10-8 mol L-1, respectively. The interference of phenolic compounds possibly present in natural water samples was investigated by using 2,6-dichlorophenol as model compound. It was showed that the interference can be eliminated by differential measurements of the analytical signal of the sample solution, before and after treatment with NaOH 0.05 mol L-1. Carbofuran contributes for the amperometric signal only when the sample solution was previously treated with NaOH 0.05 mol L-1 because of the formation of BF. Differently, the 2,6-dichlorophenol contributes to both amperometric signal of the sample solution, before and after the treatment with NaOH 0.05 mol L-1. The difference between these amperometric signals is due to the Carbofuran in the sample. Recovery studies of Carbofuran was carried out by using this methodology and natural water sample (Uberabinha river- Uberlândia-MG) fortified with Carbofuran 2.07x10-7 mol L-1 plus 2,6-diclorofenol 1.5x10-6 mol L-1. A recovery efficiency of 98.5% was found from triplicate analysis. These results shown that the methodology can be used for determination of total aryl-N-methylcarbamates in natural water samples which contains interferent phenolic compounds.